Nanodevices engineering and spin transport properties of MnBi2Te4 monolayer - Yipeng An (Nature Portfolio, 2021)
Abstract Two-dimensional (2D) magnetic materials are essential for the development of the next-generation spintronic technologies. Recently, layered van der Waals (vdW) compound MnBi2Te4 (MBT) has attracted great interest, and its 2D structure has been reported to host coexisting magnetism and topology. Here, we design several conceptual nanodevices based on MBT monolayer (MBT-ML) and reveal their spin-dependent transport properties by means of the first-principles calculations. The pn-junction diodes and sub-3-nm pin-junction field-effect transistors (FETs) show a strong rectifying effect and a spin filtering effect, with an ideality factor n close to 1 even at a reasonably high temperature. In addition, the pip- and nin-junction FETs give an interesting negative differential resistive (NDR) effect. The gate voltages can tune currents through these FETs in a large range. Furthermore, the MBT-ML has a strong response to light. Our results uncover the multifunctional nature of MBT-ML, pave the road for its applications in diverse next-generation semiconductor spin electric devices.